Assessment of chronic pain prevalence and impact on quality of life in the general population and visitors of a pain clinic in Makkah region, Saudi Arabia, 2022–2023 - Alsharif, Bayan Hashim; Bu Hamad, Zainab; Khafagy, Abuullah Ahmed; Abudawood, Abulrahman Tawfeeg; Alzahrani, Rizq Allah Abdullah B; Alghamdi, Abduljawad Hassan A (Journal of Medical Science, 2023)
Introduction. Chronic pain is a frequent, complicated, stressful health condition that significantly affects society and people. Chronic pain also is believed to be one of the most important causes of suffering and infirmity worldwide. It can impact various aspects of the person and cause emotional, social, and functional capabilities. Assessing Health-related quality of life is a significant outcome in studies concerning chronic pain patients. It is a different way to evaluate patients’ perceptions of their pain experience and its effect on their lives. Aim. The aim of this study is to establish the prevalence of chronic pain among the general population in the Makkah region, Saudi Arabia. Material and methods. An online cross-sectional study design using a structured self-administered questionnaire was distributed electronically in Arabic through social media. Results. A total of 610 participants completed the survey. Females represented 63.3% of participants, while male participants represented 36.4%. Most participants were Saudi (98.9%), and 72.3% had bachelor’s degrees or Diplomas. Single participants were almost equal to married ones (53.1 % and 46.2%, respectively), and most were nonsmokers. Conclusions. chronic pain from patients’ perspectives has physical, psychological, and social functioning and well-being effects.